Heterochrony in fringeheads (Neoclinus) and amplification of an extraordinary aggressive display in the Sarcastic Fringehead (Teleostei: Blenniiformes). (5th February 2018) - Hongjamrassilp, Watcharapong; Summers, Adam P.; Hastings, Philip A.
Abstract: The Sarcastic Fringehead ( Neoclinus blanchardi, Teleostei) exhibits an extreme version of a common aggressive display, the "gaping display, " in which an open mouth is presented toward an opponent. Males of this species have extremely long jaws that extend posteriorly well past the posterior margin of the head and are flared laterally during the gaping display. In this study, we explored morphological traits related to this extraordinary display in this and related species of blennies. Morphological modifications include enlargement of the buccopalatal membrane, elongation of the maxilla via an uncalcified posterior extension, and evolution of a novel hinge between the anterior maxilla and lacrimal bones permitting lateral movement of the upper jaw. Geometric morphometry using the truss network system, thin‐plate spline, and PCA of three closely related species of Neoclinus indicate that the elongate maxilla of N. blanchardi most likely evolved via acceleration (faster growth compared to outgroups) and hypermorphosis (continued growth to a larger body size), both forms of peramorphic heterochrony. Coloration and fluorescence of the buccopalatal membrane may also serve to amplify the extraordinary gaping display of the Sarcastic Fringehead. Abstract : The Sarcastic Fringehead ( Neoclinus blanchardi ) shows an extreme version of an aggressive gaping display. Three main features amplifying this display are an enlarged buccopalatal membrane, an elongate maxilla bone, and a notched lacrimal bone.